Exploring the Backstage of Translations: A study of translation-related manuscripts in the Anthony Burgess archives - Zanotti, Serenella; Bollettieri Bosinelli, Rosa Maria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This paper offers some preliminary considerations on the use of translators’ manuscripts in translation research. It will be argued that the importance of studying translators’ papers, aside from a philological interest, is crucial in reconstructing the prehistory and process of translations, and in analysing and evaluating the factors that influence translations, including the roles of the people involved in the translation process. More specifically, the application to translator’s manuscripts of methods of enquiry developed by genetic criticism will be illustrated in a study of the available manuscripts pertaining to the Italian translation of Anthony Burgess’s libretto Blooms of Dublin (1986). The aim of the study is to show the importance of developing a specific methodology for investigating the prehistory and process of translation. We will also argue that genetic criticism (Deppman, Ferrer, Groden 2004), while needing to be revised and adapted to the specificity of translated texts, offers a sound and effective methodology.